Analysis and Mapping of Noise Intensity on Workers' Non-Auditory Complaints at Tjoekir Sugar Factory, Jombang - Ningsih, Nurtasyia (Doctoral Program of Social Science Pasundan University, 2025)
PG Tjoekir Jombang is a sugar production company that uses production machines for cost efficiency and to increase the homogeneity of production quality. This activity causes noise exposure in the workplace which threatens the comfort and health of workers. This study aims to analyze the noise level in the work area of ??the Tjoekir Jombang Sugar Factory (PG) and its relationship to non-auditory complaints experienced by workers. The method used is a descriptive quantitative approach through direct measurement of noise using a sound level meter and distributing questionnaires to 60 respondents. The measurement results show that most work areas have noise levels exceeding the threshold of 85 dB(A) at the grinding, cooking, turning, finishing and power house stations.. Mapping using Surfer software produces 3 zones, namely high intensity levels in red > 85 dB (A), yellow to orange at 80-85 dB (A), and low levels <85 dB (A). The Chi-Square test showed a significant relationship between noise intensity and non-auditory complaints (p < 0.05). The results of the Chi-Square test showed a significant relationship between noise levels and communication disorders (p = 0.007) and psychological disorders (p = 0.033). However, the relationship with Physiological complaints was not significant (p = 0.354). These findings indicate that noise has a real impact on certain aspects of health, so appropriate control efforts need to be made.